Keeping up with the kids: the value of co-production in the study of irritability in youth depression and its underlying neural circuitry - MacSweeney, Niamh; Louvet, Perrine; Zafar, Simal; Chan, Stella W. Y.; Kwong, Alex S. F.; Lawrie, Stephen M.; Romaniuk, Liana; Whalley, Heather C. (Frontiers in Behavioral Neuroscience, 2023)
Irritability is a core symptom of adolescent depression, characterised by an increased proneness to anger or frustration. Irritability in youth is associated with future mental health problems and impaired social functioning, suggesting that it may be an early indicator of emotion regulation difficulties. Adolescence is a period during which behaviour is significantly impacted by one’s environment. However, existing research on the neural basis of irritability typically use experimental paradigms that overlook the social context in which irritability occurs. Here, we bring together current findings on irritability in adolescent depression and the associated neurobiology and highlight directions for future research. Specifically, we emphasise the importance of co-produced research with young people as a means to improve the construct and ecological validity of research within the field. Ensuring that our research design and methodology accurately reflect to lives of young people today lays a strong foundation upon which to better understand adolescent depression and identify tractable targets for intervention.